MENUMBUHKAN SEMANGAT BERWIRAUSAHA DALAM PENINGKATAN EKONOMI KELUARGA BAGI IBU PKK KAMPUNG KUPER - Aldisa Arifudin; Muhammad Awal (Musamus University, 2021)
The implementation of family economic development activities during the pandemic carried out on the PKK in Kampung Kuper. The first step taken in this devotional activity is the socialization of increasing understanding of the benefits of being a mompreneur, business opportunities and the use of technology in the pandemic period, entrepreneurship strategies and product marketing and financial management. Continued with nugget making training tofu as a business opportunity. This is expected to be a solution to increase motivation, understanding and skills and create a product to be more productive in order to improve the family economy